“Bebas Bertanggungjawab:” Responsible Waste Management dan Prilaku Konsumen Restoran Shabu & Grill Berkonsep AYCE di Makassar - Tantu, Asty Munawarti (Emik, 2025)
In recent years, the All You Can Eat (AYCE) concept restaurant has become increasingly popular as a group dining venue among Indonesian consumers, including families, teenagers, office workers and culinary enthusiasts, food vloggers, etc. where people can eat as much as they want. However, consumers cannot just take the food. While most studies on food waste focus on how restaurants' policies prevent food waste, this article not only looks at restaurant policies, but also how consumers are responsible for what they take at AYEC concept restaurant. This qualitative research was conducted on consumers of shabu & grill restaurants in Makassar, South Sulawesi, Indonesia. Informants was selested using puspossive sampling based on the criteria that they have experienced eating at AYCE restaurant. There are ten informants participated in this study, who are varied on the basis of gender (three males and seven females), age (between 21 and 30), and job (students, office workers, and general public). Data was collected using observation of dining activities and in-depth interviews, exploring their views on AYCE concept, restauran’st policy, and consumers’ responsibility (driven by individual awareness and fine system). Shabu & grill all-you-can-eat (AYCE) restaurants offer a unique dining experience for counsumers, not only in their diverse food offerings but also through specific policies: fixed pricing, self-service, time limits, and a fine system. The fixed, upfront payment allows diners to enjoy unlimited dishes, differentiating it from conventional à la carte restaurants. The self-service model provides customers with full autonomy in selecting their desired food. However, time limits necessitate self-control to prevent food waste and exceeding allocated dining durations, both of which incur fines. Consumer perspectives on the AYCE concept are twofold: food exploration and food responsibility. The former allows patrons to sample a wide array of dishes, while the latter fosters individual accountability for consumption, driven by personal awareness and the fear of penalties for leftover food or exceeding time limits. Consumers employ situational adaptation strategies to adjust behavior to AYCE demands, as well as economic calculations through careful food and portion selection to manage consumption. Consequently, AYCE restaurants operate as a "controlled freedom" environment, where the liberty to eat unlimited food is balanced by consequences for irresponsible consumption.